Nicotine: Regulatory roles and mechanisms in atherosclerosis progression. (May 2021) - Fu, Xiuxiu; Zong, Tingyu; Yang, Panyu; Li, Lin; Wang, Shizhong; Wang, Zhibin; Li, Min; Li, Xiaolu; Zou, Yulin; Zhang, Ying; Htet Aung, Lynn Htet; Yang, Yanyan; et al.
Abstract: Smoking is an independent risk factor for atherosclerosis. The smoke produced by tobacco burning contains more than 7000 chemicals, among which nicotine is closely related to the occurrence and development of atherosclerosis. Nicotine, a selective cholinergic agonist, accelerates the formation of atherosclerosis by stimulating nicotinic acetylcholine receptors (nAChRs) located in neuronal and non-neuronal tissues. This review introduces the pathogenesis of atherosclerosis and the mechanisms involving nicotine and its receptors. Herein, we focus on the various roles of nicotine in atherosclerosis, such as upregulation of growth factors, inflammation, and the dysfunction of endothelial cells, vascular smooth muscle cells (VSMC) as well as macrophages. In addition, nicotine can stimulate the generation of reactive oxygen species, cause abnormal lipid metabolism, and activate immune cells leading to the onset and progression of atherosclerosis. Exosomes, are currently a research hotspot, due to their important connections with macrophages and the VSMC, and may represent a novel application into future preventive treatment to promote the prevention of smoking-related atherosclerosis. In this review, we will elaborate on the regulatory mechanism of nicotine on atherosclerosis, as well as the effects of interference with nicotine receptors and the use of exosomes to prevent atherosclerosis development. Highlights: Nicotine accelerates the formation of atherosclerosis by stimulating nicotinic acetylcholine receptors. Nicotine can regulate the dysfunction of ECs, VSMCs and immune cells which are involved in the onset and progression of AS. Nicotine activates the expression of growth factors, ROS, and causes abnormal lipid metabolism and inflammation in AS. The review offers new perspectives for exosomes, a novel application to promote the prevention of smoking-related AS.